Work-related musculoskeletal disorders among Saudi orthopedic surgeons: a cross-sectional study - Al-Mohrej, Omar A. (Bone Jt Open, 2020)
INTRODUCTION: Studies have addressed the issue of increasing prevalence of work-related musculoskeletal (MSK) pain among different occupations. However, contributing factors to MSK pain have not been fully investigated among orthopaedic surgeons. Thus, this study aimed to approximate the prevalence and predictors of MSK pain among Saudi orthopaedic surgeons working in Riyadh, Saudi Arabia. METHODS: A cross-sectional study using an electronic survey was conducted in Riyadh. The questionnaire was distributed through email among orthopaedic surgeons in Riyadh hospitals. Standardized Nordic questionnaires for the analysis of musculoskeletal symptoms were used. Descriptive measures for categorical and numerical variables were presented. Student’s t-test and Pearson’s χ2 test were used. The level of statistical significance was set at p ≤ 0.05. RESULTS: The response rate was 80.3%, with a total number of 179 of Saudi orthopaedic surgeons (173 males and six females). Of our sample, 67.0% of the respondents complained of having MSK pain. The most commonly reported MSK pain was lower back (74.0%), followed by neck (58.2%). Age and body mass index were implicated in the development of more than one type of MSK pain. Increased years of experience (≥ 6 years) was linked to shoulder/elbow, lower back, and hip/thigh pain. Smoking is widely associated with lower back pain development, whereas physicians who do not smoke and exercise regularly reported fewer pain incidences. Excessive bending and twisting during daily practice have been correlated with increased neck pain. CONCLUSION: MSK pain was found to be common among Saudi orthopaedic surgeons. Further extensive research should be conducted to understand and analyze the risk factors involved and search for possible improvements to avoid further complications. However, ergonomics education during surgical training could be effective at modifying behaviors and reducing MSK pain manifestations.